Analisis Kecepatan dan Percepatan Gerak Robot Joules Menggunakan Metode Bilangan Kompleks - Novri Tanti (JURNAL MECHANICAL, 2014)
In general, kinematics analysis is done using graphics methods. But this method requires a substantial time in analyzing the kinematics of a mechanical system. With the development of technology, especially in the field of computers and informatics can facilitate the engineer in analyzing the kinematics. One method used with the aid of a computer program is the method of complex numbers. This study aims to analyze and compare the position, velocity, and acceleration results of the calculation method of complex numbers and methods of polygon graphics. The study was conducted on a robotic mechanical system, i.e. electric tandem bicycle partner named Robot Joules. Necessary data were analyzed using the method of complex numbers with the help of MATLAB program. Results of analysis using the method of complex numbers were compared with the results of analysis using the method of polygon graphics. For comparison, data input were made equal to the angular velocity rod 2 (ω2) of 10 rad/s and angular acceleration of rod 2 (α2) at 0 rad/s2 when bar 2 was at position angle 90 ° from the positive x-axis. Key words: kinematics, robot joules, complex numbers